Analisis Dampak Perkembangan Revolusi Industri 4.0 dan Society 5.0 Pada Perilaku Masyarakat Ekonomi (E-Commerce) - Mumtaha, Hani Atun; Khoiri, Halwa Annisa (JURNAL PILAR TEKNOLOGI : Jurnal Ilmiah Ilmu Ilmu Teknik, 2019)
Technology is one of the tools to facilitate work. The development of technology has now become a thing that is a major human need in completing work. The development of technology began with the Industrial Revolution 1.0 to the Industrial Revolution 4.0. In addition, changes in human behavior are also marked by the development of Society 5.0. The impact of technological development greatly affects the behavior of the Economic Community especially on e-commerce activities. The development of e-commerce is very dominating in Indonesia. As of March 2019, Indonesia had 30 million people who became e-commerce actors. Based on the results of a survey of 67 respondents in the scope of the University of PGRI Madiun (UNIPMA) with an average age of 19-34 years produced 43.3% of respondents chose e-commerce with the convenience obtained when dealing with e-commerce. In addition, 56.7% of respondents prefer shopping online compared to conventional shopping systems. Based on the results of the survey, the behavior of the economic community through e-commerce in Indonesia was very dominant in the era of Society5.0 because people expect ease in meeting their needs.